Method for preparing graphene and ZIF-8 composite membrane based on in-situ growth of U-shaped tube and application of graphene and ZIF-8 composite membrane
By using high-temperature heat treatment and marginalization treatment in the GO/ZIF-8 composite membrane, and growing ZIF-8 in situ in the U-shaped tube, the problems of low permeability and narrow layer spacing in the prior art were solved, and efficient gas separation selectivity and mechanical strength were achieved.
Patent Information
- Application Number
- CN202411609127.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the preparation process, the existing GO/ZIF-8 composite films cause crystals to be filled between the GO film layers, which cannot improve the permeability of the film. The stacking of GO nanosheets results in a narrow spacing, making it difficult to grow in situ.
Reduced graphene oxide (HTGO) was prepared by high-temperature heat treatment, and then marginalized treatment was performed to obtain wrinkled graphene (WG). GO and WG were mixed to prepare composite films with larger pore sizes, and ZIF-8 crystals were grown in situ through U-tubes in the porous membrane.
By growing ZIF-8 in situ, the gas separation selectivity and mechanical strength of the composite film are improved, and the gas separation selectivity of the composite film is greatly improved.
Smart Images

Figure CN119588189A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of membrane separation, and in particular to a method for preparing a graphene and ZIF-8 composite membrane based on in-situ growth of a U-shaped tube and application thereof. Background Art
[0002] Flue gas produced by the combustion of fossil fuels contains a large amount of CO2. Excessive carbon emissions have led to problems such as intensified climate change and ecological damage. In order to alleviate the problem of carbon emissions, the mixed gas produced by combustion needs to be separated. Traditional physical and chemical separation methods have disadvantages such as high energy consumption and poor selectivity, while membrane separation methods are energy-efficient, green and environmentally friendly. The interlayer spacing of graphene oxide (GO) membranes is evenly distributed and suitable for gas separation. However, the GO membrane has a certain thickness, which makes the gas molecule transmission path longer and reduces the efficiency of gas transport across the membrane. The surface of GO nanosheets contains a large number of functional groups, which can be regulated by thermal reduction, molecular cross-linking and particle intercalation to improve the interlayer channels of the membrane and enhance gas permeability.
[0003] The particle intercalation method uses ZIF-8 from the zeolite imidazolate framework (ZIF) series. Compared with other MOF materials, ZIF-8 has the advantages of suitable pore size (0.34nm), simple synthesis method, and low cost. The traditional method for preparing GO / ZIF-8 composite membranes is to first grow ZIF-8 crystals on GO nanosheets and then filter them into membranes. This method causes the GO membrane interlayers to be filled with crystals and cannot improve the permeability of the membrane. The present invention intends to adopt an in-situ growth method to first prepare a WG / GO composite membrane and then in-situ grow ZIF-8 crystals in the pores of the porous membrane.
[0004] However, the stacking of GO nanosheets results in a narrow interlayer spacing, which makes it difficult to grow in situ. The present invention first uses high temperature heat treatment to obtain reduced graphene oxide (HTGO). Then the carboxyl groups on the HTGO nanosheets are edged to obtain tile-like wrinkled graphene (WG), and finally GO and WG are mixed and filtered to prepare a composite membrane with a larger pore size. Then ZIF-8 crystals are grown in situ in the prepared porous membrane to improve the mechanical strength of the membrane. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art, and provide a method for preparing a graphene and ZIF-8 composite membrane based on in-situ growth of a U-shaped tube and an application thereof. The preparation method comprises the following steps: firstly preparing reduced graphene oxide, then preparing wrinkled graphene, mixing and dispersing the graphene and wrinkled graphene uniformly, filtering a PES base membrane and a mixed solution of graphene and wrinkled graphene to prepare a graphene and wrinkled graphene composite membrane, and finally placing the graphene and wrinkled graphene composite membrane in the middle of the U-shaped tube, adding zinc nitrate hexahydrate and 2-methylimidazole to both sides of the graphene and wrinkled graphene composite membrane respectively, and crystallizing and growing the two solutions when they are in contact in the middle of the composite membrane pores, thereby realizing in-situ growth of ZIF-8 in a porous membrane, and obtaining a graphene, wrinkled graphene and ZIF-8 composite membrane; in-situ filling of the composite membrane with ZIF-8 can maximize the spatial hindrance and selective adsorption in the channel, greatly improving the gas separation selectivity of the composite membrane, and having excellent application prospects.
[0006] In order to achieve the above technical effects, the following technical solutions are adopted:
[0007] A method for preparing a graphene and ZIF-8 composite film based on U-tube in-situ growth, the method comprising the following steps:
[0008] Step S1:
[0009] The graphene GO solution slurry is thermally reduced in an air environment. During this process, as the oxygen content decreases, the surface energy of GO increases, and the lattice begins to wrinkle, thereby obtaining heat-treated reduced graphene oxide HTGO.
[0010] Step S2:
[0011] The reduced graphene oxide HTGO material obtained in step S1 is collected, and the reduced graphene oxide HTGO material is dispersed in deionized water, and then H2O2 and MnSO4·H2O are added to obtain a mixed solution; the mixed solution is stirred at room temperature for two days to anchor more carboxyl groups at the edge of the lattice and improve its dispersibility to obtain wrinkled graphene WG;
[0012] Step S3:
[0013] The wrinkled graphene WG solution and the graphene GO solution obtained in step S2 are mixed; and deionized water is added to the mixed solution; then the mixed solution of wrinkled graphene WG and graphene GO is placed in an ultrasonic cleaner for ultrasonic dispersion; ethylenediamine EDA is added to the solution and stirred evenly to obtain a mixed solution of wrinkled graphene WG, graphene GO and ethylenediamine EDA;
[0014] Step S4:
[0015] The PES base membrane is sandwiched in the middle of the suction filtration device, and the wrinkled graphene WG and the mixed solution of graphene GO and ethylenediamine EDA prepared in step S3 are filtered to form a membrane; the membrane is removed and placed in a vacuum drying oven, and dried completely to remove the moisture inside the membrane pores, thereby obtaining a wrinkled graphene WG, graphene GO, ethylenediamine EDA composite membrane, that is, an EDA-GO / WG composite membrane;
[0016] Step S5:
[0017] The precursor zinc nitrate hexahydrate and the precursor 2-methylimidazole are respectively prepared into solutions; the wrinkled graphene WG, graphene GO, and ethylenediamine EDA composite membrane prepared in step S4 are sandwiched in the middle of a U-shaped tube, and the two precursor solutions are respectively added to both sides of the U-shaped tube; the two solutions diffuse freely, and crystallize and grow when they contact in the middle of the composite membrane pores, so as to realize the in-situ growth of ZIF-8 in the porous membrane; the composite membrane is removed and dried to obtain the graphene and ZIF-8 composite membrane, that is, the ZIF-8@EDA-GO / WG composite membrane.
[0018] Furthermore, in step S1, the concentration of the graphene GO slurry solution is 0.05 mg / ml.
[0019] Furthermore, the specific method of thermal reduction in step S1 is:
[0020] Thermal reduction was carried out in an air environment at 470°C for 120s, with a heating rate of 20°C / min.
[0021] Furthermore, in the step S2, the mass ratio of the reduced graphene oxide HTGO material, H2O2 and MnSO4·H2O is 1:4.53-18.9:0.000267-1.325, and the concentration of H2O2 is 20%-30%.
[0022] Furthermore, in step S3, the concentrations of the wrinkled graphene WG solution and the graphene GO solution are respectively 0.05 mg / ml; the mass ratio of the wrinkled graphene WG solution and the graphene GO solution is 1:1, the ultrasonic time is more than 0.5 h, and the ratio of the mass of ethylenediamine EDA to the total mass of the wrinkled graphene WG solution and the graphene GO solution is 1:100.
[0023] Furthermore, in step S4, the diameter of the PES base membrane is 25 mm, and the filtration device in step S4 is a circulating water vacuum pump; the membrane is dried at 60° C. for 12 hours to completely remove the moisture inside the membrane pores.
[0024] Furthermore, in step S5, the concentration of the precursor zinc nitrate hexahydrate is 0.025 mmol / ml; and the molar concentration ratio of the zinc nitrate hexahydrate to 2-methylimidazole is 1:35.
[0025] Furthermore, in step S5, the mixture is dried at 60° C. for 12 hours.
[0026] A graphene and ZIF-8 composite membrane is prepared based on in-situ growth of a U-shaped tube, and is prepared by any one of the above preparation methods.
[0027] A method for preparing a graphene and ZIF-8 composite membrane based on in-situ growth of a U-tube and applying the composite membrane to the separation of mixed gases; further, the mixed gas is a N2 / CO2 mixed gas.
[0028] The beneficial effects of the present invention are:
[0029] 1. The wrinkled graphene membrane is prepared by thermal reduction, which can obtain a membrane with high porosity and narrow pore size distribution;
[0030] 2. The ZIF-8@EDA-GO / WG composite membrane was prepared by the U-tube reverse diffusion method, and the reaction process can be effectively controlled according to the growth time of the crystals in the membrane.
[0031] The invention discloses a method for preparing a graphene and ZIF-8 composite membrane based on in-situ growth of a U-shaped tube and an application thereof. The preparation method comprises the following steps: firstly preparing reduced graphene oxide, then preparing wrinkled graphene, mixing and dispersing the graphene and wrinkled graphene uniformly, preparing a graphene and wrinkled graphene composite membrane by filtering a PES base membrane and a mixed solution of graphene and wrinkled graphene, and finally placing the graphene and wrinkled graphene composite membrane in the middle of the U-shaped tube, adding zinc nitrate hexahydrate and 2-methylimidazole to both sides of the graphene and wrinkled graphene composite membrane respectively, and crystallizing and growing the two solutions when they are in contact in the middle of the composite membrane pores, thereby realizing in-situ growth of ZIF-8 in the porous membrane, and obtaining a graphene, wrinkled graphene and ZIF-8 composite membrane; in-situ filling of the composite membrane with ZIF-8 can maximize the spatial hindrance and selective adsorption in the channel, greatly improving the gas separation selectivity of the composite membrane, and having excellent application prospects BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. The drawings in the following description are merely embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.
[0033] Figure 1 Schematic diagram of preparing composite membrane by U-tube reverse diffusion method of the present invention;
[0034] Figure 2 FTIR spectra of GO, EDA-GO / WG and ZIF-8@EDA-GO / WG films of the present invention;
[0035] Figure 3 XRD spectra of ZIF-8, EDA-GO / WG and ZIF-8@EDA-GO / WG (in-situ growth time is 12h, 24h and 36h respectively) of the present invention;
[0036] Figure 4 Full-spectrum XPS graphs of EDA-GO / WG and ZIF-8@EDA-GO / WG films of the present invention;
[0037] Figure 5 C1s XPS graphs of EDA-GO / WG and ZIF-8@EDA-GO / WG films of the present invention;
[0038] Figure 6 O1s XPS graph of EDA-GO / WG and ZIF-8@EDA-GO / WG films of the present invention;
[0039] Figure 7 This is the Zn 2p XPS graph of the ZIF-8@EDA-GO / WG film of the present invention;
[0040] Figure 8 The permeability and selectivity of GO, GO / WG, EDA-GO / WG and ZIF-8@EDA-GO / WG membranes of the present invention to independent CO2 or N2 gas at 0.2MPa;
[0041] Fig. 9 The permeability and selectivity of GO, GO / WG, EDA-GO / WG and ZIF-8@EDA-GO / WG membranes of the present invention to mixed CO2 / N2 gas at 0.2 MPa. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0043] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0044] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations and / or combinations thereof.
[0045] Embodiment 1:
[0046] like Figure 1 As shown, this embodiment provides a method for preparing a graphene and ZIF-8 composite film based on in-situ growth of a U-shaped tube:
[0047] Preparation method of ZIF-8@EDA-GO / WG composite membrane:
[0048] (1) The GO slurry with a concentration of 0.05 mg / ml was thermally reduced in an air environment at 470 °C for 120 s, with a heating rate of 20 °C min -1 In this process, as the oxygen content decreases, the surface energy of GO increases, and the lattice begins to wrinkle, resulting in heat-treated reduced graphene oxide (HTGO).
[0049] (2) HTGO material was collected and 40 mg of the material was dispersed in 13.33 mL of deionized water (DI), to which 0.756 g of H2O2 (H2O2 concentration was 20%-30%) and 0.0053 mg of MnSO4 were added. H2O. The mixed solution was stirred at room temperature for two days to anchor more carboxyl groups at the edge of the lattice and improve its dispersibility to obtain wrinkled graphene (WG).
[0050] (3) Taking the total mass of 0.05 mg as an example, use a pipette to take 0.5 ml of 0.05 mg / ml WG and GO solutions into a beaker, and add deionized water to the beaker until the total volume of the solution is 100 ml. Then put the GO / WG mixed solution into an ultrasonic cleaner for 0.5 h to disperse it evenly; add ethylenediamine EDA to the solution, the ratio of ethylenediamine EDA mass to the total mass of wrinkled graphene WG solution and graphene GO solution is 1:100, and stir evenly to obtain a mixed solution of wrinkled graphene WG, graphene GO and ethylenediamine EDA;
[0051] (4) A PES-based membrane (25 mm in diameter) was sandwiched in the middle of a filtration device, and the wrinkled graphene WG, graphene GO, and ethylenediamine EDA mixed solution obtained in (3) were filtered through a circulating water vacuum pump to form a membrane. The membrane was removed and placed in a vacuum drying oven, and dried at 60° C. for 12 h to completely remove the moisture inside the membrane pores, thereby obtaining an EDA-GO / WG composite membrane.
[0052] (5) The precursor zinc nitrate hexahydrate for synthesizing ZIF-8 and the precursor 2-methylimidazole are prepared into a solution at a molar concentration ratio of 1:35; wherein the concentration of zinc nitrate hexahydrate is 0.025mmol / ml; then the prepared EDA-GO / WG composite membrane is sandwiched in the middle of the U-shaped tube, and finally the two precursor solutions are added to the two ends of the U-shaped tube respectively. The two solutions diffuse freely and crystallize and grow when they contact in the middle of the composite membrane pores, realizing the in-situ growth of ZIF-8 in the porous membrane, and obtaining the GO / WG@ZIF-8 composite membrane, that is, the ZIF-8@EDA-GO / WG composite membrane.
[0053] (6) Remove the membrane and place it in a glass dish. Then place the glass dish and the membrane in a vacuum drying oven and dry them at 60°C for 12 hours to completely remove the moisture inside the membrane pores.
[0054] Preparation method of GO membrane:
[0055] Take 2 ml of GO solution with a concentration of 0.05 mg / ml and add it to a beaker, and add deionized water to the beaker until the total volume of the solution is 100 ml; ultrasonicate it for 0.5 h. Filter the evenly dispersed GO solution onto a PES-based membrane (25 mm in diameter) through a suction filter, then place it in a vacuum drying oven and dry it at 60 ° C for 12 h to complete the preparation of the GO membrane.
[0056] Embodiment 2:
[0057] 1. Characterization test:
[0058] In order to verify the possibility of ammoniation of GO / WG composite membrane and in situ growth of ZIF-8, the differences in functional groups among GO membrane, EDA-GO / WG and ZIF-8@EDA-GO / WG were analyzed by FTIR. Figure 2 As shown in the figure, compared with the GO membrane, the EDA-GO / WG membrane has a -1 and 798cm -1 New peaks appeared at 2830-2960 cm-1, representing the bending vibrations of CO and NH bonds, respectively, indicating that WG and EDA successfully introduced a large number of carboxyl and amino functional groups. After in situ growth of ZIF-8, the infrared spectrum of the ZIF-8@EDA-GO / WG film showed that the characteristic peaks of CH, Zn-N and CN were located at 2830-2960 cm-1, respectively. -1 、690cm -1 and 1042cm -1 , indicating that dimethylimidazole and zinc nitrate were successfully covalently bound in the EDA-GO / WG membrane. -1 The appearance of Zn-O peak at 1730 cm -1The right shift of the -COOH peak at 2+ It is possible that a covalent structure is formed with the carboxyl group through electrostatic adsorption. Since the carboxyl groups on the surface of graphene oxide nanosheets form hydrogen bonds and electrostatic interactions with ZIF-8, the original chemical bonding force constant K is reduced, resulting in the absorption frequency shifting to a low frequency. The above studies demonstrate the feasibility of using EDA-GO / WG membrane as a barrier to allow the precursor solution to penetrate each other on both sides of the membrane and synthesize in situ.
[0059] Next, XRD analysis was used to further verify the crystal structure of the product. Figure 3 As shown, the original EDA-GO / WG membrane only shows characteristic peaks of interlayer spacing and PES substrate at around 7° and 18°. However, after the in situ growth of ZIF-8, multiple new peaks appeared at 7.4°, 10.4°, 12.7° and 18.0°, corresponding to the (011), (022), (112) and (222) crystal planes of the ZIF-8 material, respectively. This confirms that ZIF-8 has been successfully grown in situ within the pores of the composite membrane. In order to more conveniently and intuitively study the in situ growth of ZIF-8 within the membrane pores, a more statistically significant XRD analysis was performed on the composite membranes with different in situ growth times. As shown Figure 4 As shown in the figure, the XRD peaks of ZIF-8 grown in situ in the EDA-GO / WG film for 12 h are similar to those grown in an open environment, and the characteristic peaks correspond to crystal planes such as (011), (002), and (112). This shows that at this stage, the pores do not restrict the growth of ZIF-8, and its growth mechanism is the same as in the open space, that is, nucleation growth. After 24 h of growth, the peak intensity of ZIF-8 increases proportionally, as shown by crystal planes such as (114), (223), and (134). This shows that within 24 h, the in situ growth mechanism of ZIF-8 in the membrane pores is similar to that in the bulk phase, and the crystals are smaller than the pores and are not limited by the pore size. However, after 36 h of growth, the relative peak intensity changes, and the peak of the originally lower intensity (002) increases significantly, exceeding other crystal planes. This indicates that the crystals may have filled the graphene pores, resulting in a confinement effect, and continue to grow mainly along the (002) crystal plane.
[0060] In addition, XPS was used to analyze the interaction between ZIF-8 nanoparticles and the membrane by detecting the changes in element content, oxidation state, and peak shift of the EDAGO / WG membrane before and after in situ growth of ZIF-8. Figure 5 and Figure 6 As shown in the full spectrum and C1s analysis, the N signal of ZIF-8@EDA-GO / WG film at 400eV is significantly enhanced compared with that of EDA-GO / WG film, and new Zn signals appear at 1021.70eV and 1044.76eV. Figure 7The expansion of the CN / CO related peak area at 285.64 eV can be observed, which is due to the introduction of ZIF-8 containing some CN bonds, resulting in a slight increase in the CO / CN related peak area. In the O1s spectrum, compared with the EDAGO / WG membrane, the peak areas of CO and C—O in the ZIF-8@EDA-GO / WG membrane did not change much, but the peak position moved toward the lower energy direction, indicating that there is a strong interaction between the CO and C—O functional groups on the GO / WG layer and other electronegative groups. This leads to an increase in the electron cloud density around the O atom, weakening its binding energy with the innermost electrons. From Figure 7 It can be clearly seen that these electronegative groups and Zn 2+ Combined, a strong interaction is formed in the form of Zn-O covalent bonds.
[0061] 2. Performance Testing
[0062] To clarify the function of each membrane component, we conducted a detailed comparison of the permeance and CO2 / N2 selectivity of GO membrane, GO / WG membrane, EDA-GO / WG membrane, and ZIF-8@EDAGO / WG membrane. Figure 8 As shown in Figure 2, pure GO membranes exhibit low N2 / CO2 permeability (CO2: 100 GPU, N2: 400 GPU) and selectivity due to the obstruction of sub-nanometer 2D channels and the limited number of carboxyl groups. With the introduction of WG, the large number of 1 nm channels formed by wrinkles significantly improved the permeability of the composite membrane, and the CO2 and N2 fluxes increased from 100 GPU and 400 GPU to 1600 GPU and 2700 GPU, respectively. However, the enlarged channel size reduced the N2 / CO2 selectivity, indicating that the main role of WG is to form pores and improve permeability.
[0063] In addition, with the addition of cationic crosslinker EDA, the permeability of the composite membrane to single N2 / CO2 gas decreased, CO2 flux and N2 flux decreased from 1600GPU and 2700GPU (GO / WG membrane) to 900GPU and 2300GPU, respectively, and the selectivity increased to 2.55. This indicates that the modification of the pore wall by EDA produces a steric hindrance effect on the gas molecules, and the affinity of EDA for CO2 further reduces the transmission of CO2 in the pores, thereby improving the selectivity. Therefore, EDA can not only act as a crosslinker to enhance the mechanical properties of the composite membrane, but also provide steric hindrance and selective adsorption to improve the separation efficiency. After in-situ filling of ZIF-8 in a confined space, the N2 permeability decreased slightly from 2300GPU (EDA-GO / WG) to 1900GPU, the CO2 flux decreased sharply from 900GPU to 49GPU, and the N2 / CO2 selectivity increased significantly to 18.3. The results show that in-situ filling of ZIF-8 can maximize the steric hindrance and selective adsorption in the channel, greatly improving the selectivity of the composite membrane. In order to verify the actual gas separation performance, we also tested the mixed gas and obtained the following results: Fig. 9 Similar trends are shown.
[0064] In summary, the present invention discloses a method for preparing a graphene and ZIF-8 composite membrane based on in-situ growth of a U-shaped tube and an application thereof. The preparation method comprises the following steps: firstly preparing reduced graphene oxide, then preparing wrinkled graphene, mixing and dispersing the graphene and wrinkled graphene uniformly, preparing a graphene and wrinkled graphene composite membrane by filtering a PES base membrane and a mixed solution of graphene and wrinkled graphene, and finally placing the graphene and wrinkled graphene composite membrane in the middle of the U-shaped tube, adding zinc nitrate hexahydrate and 2-methylimidazole to both sides of the graphene and wrinkled graphene composite membrane respectively, and crystallizing and growing the two solutions when they are in contact in the middle of the composite membrane pores, thereby realizing in-situ growth of ZIF-8 in the porous membrane, and obtaining a graphene, wrinkled graphene and ZIF-8 composite membrane; in-situ filling of the composite membrane with ZIF-8 can maximize the spatial hindrance and selective adsorption in the channel, greatly improving the gas separation selectivity of the composite membrane, and having excellent application prospects.
[0065] At this point, those skilled in the art recognize that, although the embodiments of the present invention have been shown and described in detail herein, many other variations or modifications that conform to the principles of the present invention can still be directly determined or derived based on the contents disclosed in the present invention without departing from the spirit and scope of the present invention. Therefore, the scope of the present invention should be understood and recognized as covering all such other variations or modifications.
Claims
1. A method for preparing a graphene and ZIF-8 composite film based on U-tube in-situ growth, characterized in that: The method comprises the following steps: Step S1: The graphene GO solution slurry is thermally reduced in an air environment. During this process, as the oxygen content decreases, the surface energy of GO increases, and the lattice begins to wrinkle, thereby obtaining heat-treated reduced graphene oxide HTGO. Step S2: The reduced graphene oxide HTGO material obtained in step S1 is collected, and the reduced graphene oxide HTGO material is dispersed in deionized water, and then H2O2 and MnSO4·H2O are added to obtain a mixed solution; the mixed solution is stirred at room temperature for two days to anchor more carboxyl groups at the edge of the lattice and improve its dispersibility to obtain wrinkled graphene WG; Step S3: The wrinkled graphene WG solution and the graphene GO solution obtained in step S2 are mixed; and deionized water is added to the mixed solution; then the mixed solution of wrinkled graphene WG and graphene GO is placed in an ultrasonic cleaner for ultrasonic dispersion; ethylenediamine EDA is added to the solution and stirred evenly to obtain a mixed solution of wrinkled graphene WG, graphene GO and ethylenediamine EDA; Step S4: The PES base membrane is sandwiched in the middle of the suction filtration device, and the wrinkled graphene WG and the mixed solution of graphene GO and ethylenediamine EDA prepared in step S3 are filtered to form a membrane; the membrane is removed and placed in a vacuum drying oven, and dried completely to remove the moisture inside the membrane pores, thereby obtaining a wrinkled graphene WG, graphene GO, ethylenediamine EDA composite membrane, that is, an EDA-GO / WG composite membrane; Step S5: The precursor zinc nitrate hexahydrate and the precursor 2-methylimidazole are respectively prepared into solutions; the wrinkled graphene WG, graphene GO, and ethylenediamine EDA composite membrane prepared in step S4 are sandwiched in the middle of a U-shaped tube, and the two precursor solutions are respectively added to both sides of the U-shaped tube; the two solutions diffuse freely, and crystallize and grow when they contact in the middle of the composite membrane pores, so as to realize the in-situ growth of ZIF-8 in the porous membrane; the composite membrane is removed and dried to obtain the graphene and ZIF-8 composite membrane, that is, the ZIF-8@EDA-GO / WG composite membrane.
2. A method for preparing a graphene and ZIF-8 composite film based on U-tube in-situ growth as described in claim 1, characterized in that: The concentration of the graphene GO slurry solution in step S1 is 0.05 mg / ml.
3. A method for preparing a graphene and ZIF-8 composite film based on in-situ growth of a U-tube as described in claim 1, characterized in that: The specific method of thermal reduction in step S1 is: Thermal reduction was carried out in an air environment at 470°C for 120s, with a heating rate of 20°C / min.
4. A method for preparing a graphene and ZIF-8 composite film based on U-tube in-situ growth as claimed in claim 1, characterized in that: In the step S2, the mass ratio of the reduced graphene oxide HTGO material, H2O2 and MnSO4·H2O is: 1: 4.53-18.9: 0.000267-1.325, and the concentration of H2O2 is 20%-30%.
5. A method for preparing a graphene and ZIF-8 composite film based on U-tube in-situ growth as claimed in claim 1, characterized in that: In the step S3, the concentrations of the wrinkled graphene WG solution and the graphene GO solution are respectively 0.05 mg / ml; the mass ratio of the wrinkled graphene WG solution and the graphene GO solution is 1:1, the ultrasonic time is more than 0.5 h, and the ratio of the mass of ethylenediamine EDA to the total mass of the wrinkled graphene WG solution and the graphene GO solution is 1:
100.
6. A method for preparing a graphene and ZIF-8 composite film based on in-situ growth of a U-tube as described in claim 1, characterized in that: The diameter of the PES base membrane in step S4 is 25 mm, and the filtration device in step S4 is a circulating water vacuum pump; the membrane is dried at 60° C. for 12 hours to completely remove the moisture inside the membrane pores.
7. A method for preparing a graphene and ZIF-8 composite film based on in-situ growth of a U-tube as described in claim 1, characterized in that: The concentration of the precursor zinc nitrate hexahydrate in step S5 is 0.025 mmol / ml; the molar concentration ratio of the zinc nitrate hexahydrate to 2-methylimidazole is 1:
35.
8. A method for preparing a graphene and ZIF-8 composite film based on in-situ growth of a U-tube as described in claim 1, characterized in that: In the step S5, the mixture is dried at 60° C. for 12 hours.
9. A method for preparing a graphene and ZIF-8 composite membrane based on in-situ growth of a U-tube, characterized in that: The composite film is prepared by any one of the preparation methods in claims 1-8.
10. The use of a graphene and ZIF-8 composite membrane prepared by in-situ growth of a U-tube in separation of mixed gases as claimed in claim 9, characterized in that: The mixed gas is N2 / CO2 mixed gas.
Citation Information
Patent Citations
Method for preparing ZIF-8@graphene oxide hybrid membrane through nano region-limiting in-situ growth
CN109012224A
Graphene nanoscale porous film, preparation method and application
CN113304624A
Method for efficiently and rapidly preparing two-dimensional vertical heterojunction separation membrane
CN114288866A
Ultrathin defect-free ZIFs-GO composite membrane, preparation method and application thereof
CN116371213A
High-permeability ZIF-67 separation membrane, preparation method and application
CN118663095A